Analisis Kemampuan Berpikir Kritis Siswa Pada Aspek Advanced Clarification dan Inference pada Konsep Sistem Pencernaan Di Kelas XI MIPA SMA Negeri 2 Tanjungpinang - Oktaviani Dwi Putri; Nevrita; Nur Eka Kusuma Hindrasti (Department of Biology Education, Faculty of Education and teacher Training, Maritime University of Raja Ali Haji, 2019)
ABSTRACT: The purpose of this study is to describe students' critical thinking skills in the aspects of advanced clarification and inference of the XI MIPA class of SMA Negeri 2 Tanjungpinang. The population of this study were all students of class XI MIPA of SMA Negeri 2 Tanjungpinang consisting of 7 classes with a total of 259 students. The sample in this study amounted to 146 taken with cluster random sampling techniques. Data collection techniques through tests in the form of questions were developed using indicators of critical thinking skills. Test instruments are used to determine students' critical thinking skills in the aspects of advanced clarification and inference. Based on data analysis, it is known that the average percentage in the advanced clarification aspect is 63% with a category and 62% inference. So the conclusion in this study that the ability to think critically in the advanced clarification and inference aspects of class XI MIPA students of SMA Negeri 2 Tanjungpinang in the category is quite critical. ABSTRAK: Tujuan penelitian ini untuk mendeskripsikan kemampuan berpikir kritis siswa pada aspek advanced clarification dan inference kelas XI MIPA SMA Negeri 2 Tanjungpinang. Populasi penelitian ini adalah seluruh siswa kelas XI MIPA SMA Negeri 2 Tanjungpinang yang terdiri dari 7 kelas dengan total 259 siswa. Sampel dalam penelitian ini berjumlah 146 yang diambil dengan teknik cluster random sampling. Teknik pengumpulan data melalui tes berupa soal yang dikembangkan menggunakan indicator kemampuan berpikir kritis. Intrumen tes digunakan untuk mengetahui kemampuan berpikir kritis siswa pada aspek advanced clarification dan inference. Berdasarkan analisis data maka diketahui rata-rata persentase pada aspek advanced clarification adalah 63% dengan kategori dan inference 62%. Maka kesimpulan dalam penelitian ini bahwa kemampuan berpikir kritis pada aspek advanced clarification dan inference siswa kelas XI MIPA SMA Negeri 2 Tanjungpinang pada kategori cukup kritis.